On the importance of early testing even when imperfect in a pandemic such as COVID- 19 (2020)
As the COVID-19 pandemic unfolds, health departments rely upon accurate surveillance systems to characterize local, regional, and national cases of the disease.With heterogenous symptomology, including asymptomatic transmission, individuals may or may not receive diagnostic laboratory testing. The case definition offered by the World Health Organization, and adopted by many health departments in the U.S., only confirms a case based on a positive diagnostic test; an inconclusive test or unavailable test may be labeled a probable case [1]. A false negative test result may not be identified as a case altogether. Early on in the pandemic when the capacity for testing was limited, the Centers for Disease Control and Prevention advised a priority-based approach to testing for the SARS-CoV-2 virus, the etiologic agent of COVID-19 disease, based on age, occupation, and morbidity [2]. Among those tested, the accuracy of the laboratory assay for SARSCoV-2 can make the difference between a false positive based on the clinical findings that are attributable to another cause, or a false negative based on lack of clinical findings that are attributable to SARS-CoV-2. As such, testing has crucial implications on surveillance so that we can formulate a more informed response to the pandemic. Indeed, prior work has demonstrated the potential for profound bias in epidemic curves constructed from inaccurate COVID-19 surveillance data